2012
DOI: 10.1590/s1984-82502012000400018
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion and biofilm formation by Staphylococcus aureus from food processing plants as affected by growth medium, surface type and incubation temperature

Abstract: This study assessed the effect of different growth media [BHI broth, BHI broth plus glucose (10 g/100 mL) and BHI broth plus NaCl (5 g/100 mL)] and incubation temperatures (28 or 37 ºC) on the adherence, detachment and biofilm formation on polypropylene and stainless steel surfaces (2 x 2 cm coupons) for a prolonged period (24-72 h) by some strains of Staphylococcus aureus (S3, S28 and S54) from food processing plants. The efficacy of the sanitizers sodium hypochlorite (250 mg/mL) and peracetic acid (30 mg/mL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…However, no difference was observed between 25 and 37 8C (P > 0.05). Similar results were obtained by Jeronimo et al, (2012), who found no difference between 28 and 37 8C on the adherence capability of S. aureus. We detected cell viability of the isolates in biofilm using the MTT assay (Fig.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…However, no difference was observed between 25 and 37 8C (P > 0.05). Similar results were obtained by Jeronimo et al, (2012), who found no difference between 28 and 37 8C on the adherence capability of S. aureus. We detected cell viability of the isolates in biofilm using the MTT assay (Fig.…”
Section: Resultssupporting
confidence: 88%
“…The biofilm forming capacity of S. aureus has been affected by several factors such as the nature of the surface, the growth medium, and other environmental conditions (Jeronimo et al, 2012;Zhao et al, 2017). In a study, most S. aureus strains produced more biofilm at 37 8C than at 25 8C, and showed better biofilm production with addition of glucose (Vazquez-Sanchez et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The assayed strains revealed high capacities to adhere and form biofilms on polypropylene and stainless steel surfaces under different growth conditions, and the cells in biofilm matrixes were resistant to total removal when exposed to the sanitizers such as sodium hypochlorite and peracetic acid (Souza et al, 2014;Jerônimo et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…1). Different strains of S. aureus were characterized by intensive reversible attachment to surfaces which depends on the surface properties, available nutrients, mobility of the environment, exposure temperature and time [47][48][49]. In the presence of nutrients and under static conditions, S. aureus cells are fixed in large numbers on some surfaces [47][48][49].…”
Section: Attachment and Growth Of Bacteria On Apple Fruitsmentioning
confidence: 99%
“…Different strains of S. aureus were characterized by intensive reversible attachment to surfaces which depends on the surface properties, available nutrients, mobility of the environment, exposure temperature and time [47][48][49]. In the presence of nutrients and under static conditions, S. aureus cells are fixed in large numbers on some surfaces [47][48][49]. In this experiment, the weaker attachment of S. aureus and its easier removal from the apple surface by swabbing were probably caused by limited nutrients and the occasional shaking of the solution with the apples.…”
Section: Attachment and Growth Of Bacteria On Apple Fruitsmentioning
confidence: 99%